Using VBA Learning Media To Improve Students’ Mathematical Understanding Ability - Tommy Tanu Wijaya; Zhou Ying; Liu Cunhua; Zulfah Zulfah (Departement of Mathematics Education, 2020)
Trigonometry is one of the basic of mathematics that is taught in high school. Students always thinks that trigonometry is a hard theory and this research aims to overcome the students’ problems by using VBA learning media base on the 6-question cognitive theory. This research will use the experiment method with a pre-test and post-test to see the difference on the students’ mathematics understanding ability that uses VBA learning media based on the 6-question cognitive theory and the one that uses traditional teaching method. The result of this research is that there is a difference and an increase in the students’ mathematics understanding ability that uses VBA learning media base on the 6-question cognitive theory compared to the students who uses traditional teaching method.